Spatial characteristics of industrial economic location and its formation in Chongqing, China - Tang, Zhonglin; Fu, Min; Wang, Yuting; Zhao, Yihui (Frontiers in Environmental Science, 2023)
As the core carrier and organizational bodies of the regional industrial space, the study of the location of industrial enterprises and the formation of their economic location is related to the rational development of regional industries, the coordination of human and environment, and the effective allocation of resources. Taking Chongqing, one of the six old industrial bases in China, as an example, this study analyzed the spatial distribution characteristics, economic location characteristics and formation laws of industrial enterprises based on the Points of interest data(POI), and investigation data. The results showed that industrial enterprises in Chongqing show obvious spatial clustering characteristics, about 93.50%, 60.34%, 96.67%, 97.57%, 73.57%, 64.83% of industrial enterprises were distributed within the spatial range of 10 Km from the motorways, national highways, provincial highways, county highways, main streams of rivers and central towns, and 93.48% of industrial enterprises were distributed at an altitude of 800 meters or less. In order to further reveale the economic location characteristics of industrial enterprises in Chongqing, this study further quantified the spatial differentiation law of industrial economic location based on Geographically weighted regression(GWR). The results showed that factors such as the Distance to National Highways (DNH), Distance to County Highways (DCH), Distance to Central Towns (DCC), Distance to River systems (DR), and Population Density (POP) had significant positive impacts on the formation of economic locations of industrial enterprises, while the Distance to Motorway(DMW) exerted a certain negative influence, but the effectiveness sees strong spatial heterogeneity according to the type of industry and the actual regional industrial development, with factors such as transportation accessibility, environment, and labor force playing a moderating role.